Influence of facilities performance on student’s satisfaction in Northern Nigerian universities: Results from interim study - Abdullahi, Isa; Wan Yusoff, Wan Zahari (Emerald, 2019)
Purpose – Higher institutions in Nigeria have witnessed an increase in the number of student enrolments; Northern Nigerian universities are not excluded. As the number of students increases, so do their needs in terms of facilities such as lecture halls, libraries, laboratories, accommodation, studios, furniture and other auxiliary facilities services (among others things). The purpose of this study is to explore the structural characteristics of building features’ performance and to statistically group them into building components (dependent) and physical and non-physical building features (independent) constructs, relating to influence of facilities’ performance in student satisfaction in Northern Nigerian universities.